2007
DOI: 10.1002/cncr.22594
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer screening with annual transvaginal sonography

Abstract: BACKGROUNDOvarian cancer has the highest mortality rate of all gynecologic malignancies, and most women present with advanced‐stage disease. The current investigation was performed to determine the efficacy of annual transvaginal sonography (TVS) as a screening method for ovarian cancer.METHODSAnnual TVS screening was performed on 25,327 women from 1987 to 2005. Asymptomatic women aged ≥50 years and women aged ≥25 years who had a family history of ovarian cancer were eligible for participation in this trial.RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
150
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(159 citation statements)
references
References 41 publications
2
150
0
7
Order By: Relevance
“…Furthermore, we would have to perform multiple studies prospectively on a larger scale with larger patient population to assess the reliability of both forms of imaging, that is, color Doppler and grey scale imaging independently as well as concurrently with a predefined criteria in determining the diagnosis of ovarian masses (Van Nagell et al, 2007). Knowledge of the exact nature of a pelvic mass after ultrasound examination is also a prerequisite for effective management, surgical or non-surgical.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we would have to perform multiple studies prospectively on a larger scale with larger patient population to assess the reliability of both forms of imaging, that is, color Doppler and grey scale imaging independently as well as concurrently with a predefined criteria in determining the diagnosis of ovarian masses (Van Nagell et al, 2007). Knowledge of the exact nature of a pelvic mass after ultrasound examination is also a prerequisite for effective management, surgical or non-surgical.…”
Section: Discussionmentioning
confidence: 99%
“…A future step could be the earlier referral of such patients for ovarian cancer screening. According to van Nagell et al (22), if a correlation was found between hypodontia and ovarian cancer in more prospective studies, then semiannual screening should become the standard of care for those women in order to achieve earlier detection. Before reaching any conclusion, there are several limitations that should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…One of the longer running series has been in Kentucky, USA, which started in 1987, used annual transvaginal ultrasound scanning and continued until 2005 (DePriest andDeSimone 2003;van Nagell et al 2007). A total of 25,327 women underwent screening and 364 (1.4%) had persisting ovarian abnormality; these women underwent CA125 estimation, tumour morphology indexing (ovarian volume, cyst wall and septation) and Doppler fl ow sonography, prior to laparoscopy or laparotomy.…”
Section: Editorialmentioning
confidence: 99%